Development Of The Digital Economy As The Basis Of The Knowledge Economy - N.I. Khasankhonova; O. Mamadiyorov (International Scientific and Current Research Conferences, 2020)
The digital economy leads to economic growth, both in an individual country and in the whole world. This article examines the development of the digital economy as the foundation of the knowledge economy.